Design and experiment of a new solar air heating collector. (1st April 2016) - Shams, S.M.N.; Mc Keever, M.; Mc Cormack, S.; Norton, B.
Abstract: This paper presents the design and experiment of a CTAH (Concentrating Transpired Air Heating) system. A newly designed solar air heating collector comprised of an inverted perforated absorber and an asymmetric compound parabolic concentrator was applied to increase the intensity of solar radiation incident on the perforated absorber. An extensive literature review was carried out to find the vital factors to improve optical and thermal efficiency of solar air heating systems. A stationary optical concentrator has been designed and experimented. Experimental thermal efficiency remained high at higher air flow rates. The average thermal efficiency was found to be approximately 55%–65% with average radiation above 400 W/m 2 for flow rates in the range of 0.03 kg/s/m 2 to 0.09 kg/s/m 2 . Experimental results at air flow rates of 0.03 kg/s/m 2 and 0.09 kg/s/m 2 showed temperature rise of 38 °C and 19.6 °C respectively at a solar radiation intensity of 1000 W/m 2 . A comparative performance study shows the thermal performance of CTAH. As the absorber of the CTAH facing downward, it avoids radiation loss and the perforated absorber with tertiary concentrator reduces thermal losses from the system. Highlights: Literature review was carried out to improve SAH system performance. Optimisation factors were optical efficiency; heat loss, weight and cost. Concentrator was designed to concentrate radiation for 6–7 h. The highest efficiency of CTAH can be 73%. It can work as efficient as 60% for a temperature rise of 70 °C.